Louie's goose - Ehrlich, H. M.; Bolam, Emily (Boston : Houghton Mifflin, 2000)
While spending the summer at the beach with his parents, Louie has a wonderful time playing with his toy goose and even rescues her from a big wave.
AD 380
Keywords: Toys -- Fiction; Geese -- Fiction; Beaches -- Fiction